A systematic review of interventions to improve knowledge and self-management skills concerning contraception, pregnancy and breastfeeding in people with rheumatoid arthritis - Ackerman, I.; Ngian, G.; Van Doornum, S.; Briggs, Andrew (2015)
This systematic review aimed to determine the effectiveness of interventions for improving knowledge and/or self-management skills concerning contraception, pregnancy and breastfeeding in people with rheumatoid arthritis (RA). We searched four databases (MEDLINE, CINAHL, Cochrane Trials, PsycINFO) using a comprehensive search strategy. Studies were eligible if they were prospective, published in English from 2004 to 2015, included participants with RA and tested an intervention designed to improve knowledge and/or self-management skills relating to family planning, pregnancy or breastfeeding. As no studies met the latter criterion, the search strategy was expanded to include all prospective studies evaluating RA educational and/or self-management interventions. Data on study characteristics, participant characteristics and programme content were extracted to summarise the evidence base for interventions to support people with RA during their reproductive years. Expanded literature searches identified 2290 papers, of which 68 were eligible. Of these, nine papers (13 %) specifically excluded pregnant women/breastfeeding mothers or recruited only older people.Only one study (1 %) explicitly evaluated pregnancy-focused education via a motherhood decision aid, while eight studies (12 %) incorporated relevant (albeit minor) components within broader RA educational or self-management interventions. Of these, three studies provided methotrexate education in relation to conception/pregnancy/breastfeeding; three incorporated discussions on RA and relationships, impact of RA on the family or sexual advice; one provided information regarding contraception and fertility; and one issued a warning regarding use of biologic therapy in pregnancy/breastfeeding. In conclusion, information regarding family planning, pregnancy or breastfeeding represents a negligible part of published RA educational interventions, with scope to develop targeted resources.